'Insiders' and 'outsiders' in the study of African traditional religions: one more time! - Chitando, Ezra (Missionalia, 2001)
African Traditional Religions (ATRs) have become an integral part the curriculum for many Departments, of Religious Studies and Theology across Africa. This article highlights the debate generated between African and Western scholars.
free
Keywords: Africa – Religion – Study and teaching; Learning and scholarship; Religions – Study and teaching – Methodology